Continuous negative external pressure (cNEP) reduces respiratory impairment during screening colonoscopy: a pilot study - Kais, Susan S.; Klein, Kenneth B.; Rose, Richard M.; Endemann, Sarah; Coyle, Walter J. (Endoscopy, 2016)
Background and study aims: Drugs administered during gastrointestinal procedures cause increased collapsibility of the upper airway, which may lead to respiratory impairment. We evaluated the ability of continuous negative external pressure (cNEP) to lessen respiratory impairment during screening colonoscopy.Patients and methods: The initial 24 patients served as controls, while the next 30 received cNEP. cNEP was delivered by a soft silicone collar placed over the anterior neck. The primary endpoint was the frequency of respiratory impairment, defined as either: (i) a decline from baseline of > 4 % in oxygen saturation, or (ii) apnea lasting ≥ 20 seconds.Results: Mean respiratory impairment episodes were 3.50 in the no-cNEP group vs. 1.92 in the cNEP group, a reduction of 45 % (P = 0.022). Apneas ≥ 20 seconds occurred in 74 % of the no-cNEP group and 28 % of the cNEP group (P = 0.002). While 42 % of the no-cNEP group required increased supplemental oxygen, this was true for only 10 % of the cNEP group (P = 0.01). cNEP adverse events were minimal. Conclusions: During screening colonoscopy, sedation-related respiratory impairment is significantly reduced by cNEP.ClinicalTrials.gov NCT01895062.